The The Development of E-Commerce and Digital Transactions in The Dynamics Of Civil Law and Personal Data Protection Law - Afda'u, Faisal; Wahyuni, Husnia Hilmi (Kadiri Islamic University, 2025)
This research aims to identify and analyze the impact of the development of e-commerce and digital transactions on the regulation and implementation of civil law in Indonesia, and to assess the extent to which personal data protection law provides legal certainty and protection for consumers in e-commerce transactions. The research method used is normative juridical with statutory and conceptual approaches. The analysis focuses on the legal norms surrounding e-commerce and digital transactions from the perspectives of civil law and personal data protection, utilizing primary legal sources in the form of updated legislation and secondary sources such as literature and legal journals. The results indicate that the evolution of e-commerce has brought fundamental changes to Indonesian civil law. The Indonesian Civil Code (KUHPer), which originally only regulated physical transactions, is now supplemented by specific regulations such as Law Number 1 of 2024 concerning Electronic Information and Transactions (ITE Act) and Law Number 27 of 2022 concerning Personal Data Protection (PDP Act). These regulations recognize the legal validity of electronic documents, signatures, and evidence. Civil law has adapted to address issues of digital evidence, digital contracts, cross-border jurisdiction, and alternative online dispute resolution. Consumer protection has also been strengthened through requirements for transparency and data security. This transformation provides legal certainty while supporting a secure digital economic ecosystem.